Tingkat Pengetahuan Mengenai Hipertensi dan Pola Kepatuhan Pengobatan pada Penderita Hipertensi yang Berkunjung ke Tenda Tensi Tim Bantuan Medis Janar Duta Fakultas Kedokteran Universitas Udayana - Hakna Sihombing, Theresia Fitri; Artini, I Gusti Ayu (E-Jurnal Medika Udayana; Vol 6 No 12 (2017): E-Jurnal Medika Udayana, 2017)
Hypertension that is not handled properly will cause adverse complications, and good medication adherence can prevent these complications. Knowledge of hypertension is known as one of the factors associated with medication adherence of hypertensive patients. This study aims to determine the pattern of treatment complianced and the level of patient knowledge about hypertension and its treatment in patients who visited the Tenda Tensi Janar D?ta Medical Assistance Team Medical Faculty Udayana University. This study was a descriptive observational research with cross sectional approach. Among 70 samples of the study, most of the samples were aged 40-59 years (70%),) men (58.6%), achieved higher education level (75.7%), self-employed (47.1%), has grade two hypertension when visiting (47.1%), and using captopril user (37.1%). Most patients have a good knowledge (82.9%), but most patients were not adherent to medication (84.3%). Keyword : Hypertension, medication adherence, knowledge